Secreted Amyloid Precursor Protein-Alpha Enhances LTP Through the Synthesis and Trafficking of Ca2+-Permeable AMPA Receptors - Livingstone, Rhys W.; Elder, Megan K.; Singh, Anurag; Westlake, Courteney M.; Tate, Warren P.; Abraham, Wickliffe C.; Williams, Joanna M. (Frontiers in Molecular Neuroscience, 2021)
Regulation of AMPA receptor expression by neuronal activity and neuromodulators is critical to the expression of both long-term potentiation (LTP) and memory. In particular, Ca2+-permeable AMPARs (CP-AMPAR) play a unique role in these processes due to their transient, activity-regulated expression at synapses. Secreted amyloid precursor protein-alpha (sAPPα), a metabolite of the parent amyloid precursor protein (APP) has been previously shown to enhance hippocampal LTP as well as memory formation in both normal animals and in Alzheimer’s disease models. In earlier work we showed that sAPPα promotes trafficking of GluA1-containing AMPARs to the cell surface and specifically enhances synthesis of GluA1. To date it is not known whether de novo synthesised GluA1 form CP-AMPARs or how they contribute to sAPPα-mediated plasticity. Here, using fluorescent non-canonical amino acid tagging–proximity ligation assay (FUNCAT-PLA), we show that brief treatment of primary rat hippocampal neurons with sAPPα (1 nM, 30 min) rapidly enhanced the cell-surface expression of de novo GluA1 homomers and reduced levels of de novo GluA2, as well as extant GluA2/3-AMPARs. The de novo GluA1-containing AMPARs were localised to extrasynaptic sites and later internalised by sAPPα-driven expression of the activity-regulated cytoskeletal-associated protein, Arc. Interestingly, longer exposure to sAPPα increased synaptic levels of GluA1/2 AMPARs. Moreover, the sAPPα-mediated enhancement of LTP in area CA1 of acute hippocampal slices was dependent on CP-AMPARs. Together, these findings show that sAPPα engages mechanisms which specifically enhance the synthesis and cell-surface expression of GluA1 homomers, underpinning the sAPPα-driven enhancement of synaptic plasticity in the hippocampus.